A Galileo Forgery. Unmasking the New York Sidereus Nuncius - Bredekamp, Horst (Galileo's O, 2014)
In this work, historians in various fields revise the results presented in the first two volumes of the series, which analyzed the New York copy of Sidereus Nuncius. While many of their findings remain valid, the subject of analysis proved to be a forgery. Volume III describes how the discovery of forgery was made - a watershed moment in the continuing struggle between forgers and those who seek to apprehend them.